Penyusunan Laporan Keuangan Pondok Pesantren Hajar Aswad Gunungkidul Berdasarkan Pedoman Akuntansi Pesantren - Wihdah Salsabila; Safaah Restuning Hayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Islamic boarding schools are non-profit organizations operating in the fields of education and religion. Non-profit organizations are organizations that are run by seeking their own capital by increasing profits, receiving donations from individuals or groups. Therefore, it is necessary to record cash disbursements as a form of accountability and transparency to related parties. This research aims to analyze the financial reports of the Hajar Aswad Islamic Boarding School and describe the preparation of the financial reports of the Hajar Aswad Islamic Boarding School based on the Islamic Boarding School Accounting Guidelines. This research uses a qualitative descriptive research method. The data used is primary and secondary data. Data collection was obtained through observation, interviews and documentation techniques and its validity was tested using the technical triangulation method. The data analysis technique uses qualitative analysis techniques, namely the stages of data reduction, data presentation, and drawing conclusions/verification. The results of this research found that the Hajar Aswad Islamic Boarding School was deemed not to have presented adequate financial reports and was not based on the Islamic Boarding School Accounting Guidelines because the Islamic boarding school did not know and understand the Islamic Boarding School Accounting Guidelines. The Hajar Aswad Islamic Boarding School only presents a cash flow report containing information on cash in and cash out, while the financial position report, activity report and notes to the financial report have not been presented.